Contribution to the knowledge of Carabidae in Iran with the descriptions of five new taxa, proposing of four synonyms and providing of nine new records (Insecta: Coleoptera) - Muilwijk, Jan; Seiedy, Marjan; Wrase, David W. (Zootaxa, 2021)
A contribution to the knowledge of the ground beetles in Iran is given. The ground beetle diversity in Iran is rich, with 1135 known species and subspecies in total so far, and 20% percent of them are endemic. However, the Iranian fauna is still not well known. In this paper, five new taxa of ground beetles are described: Leistus (Pogonophorus) spinibarbis zagrosensis ssp. n., Trechus kouroshi sp. n., Atranus dariushi sp. n. from Zagros, and Philorhizus flavocorpus sp. n. and Philorhizus kermanus sp. n. from Kerman; four new synonyms are established: Poecilus (Ancholeus) aeneolus (Chaudoir, 1868) syn. n. and Poecilus (Ancholeus) hafezi (Morvan, 1975) syn. n. = Poecilus (Ancholeus) puncticollis (Dejean, 1828); Poecilus (Ancholeus) iranicus (Morvan, 1974) syn. n. = Poecilus (Derus) advena (Quensel, 1806), and Olegius turkmenicus Komarov, 1996 syn. n. = Pogonopsis pallida Bedel, 1898; and the first records of nine species for Iran are provided: Porotachys ottomanus ssp. ottomanus Schweiger, 1968, Tachyura (Tachyura) shahinei (Schatzmayr & Koch, 1934), Tachyura (Tachyura) conspicua (Schaum, 1863), Polyderis algiricus (Lucas, 1846), Polyderis impressipennis (Motschulsky, 1860), Pogonopsis pallida Bedel, 1898, Chlaenius (Trichochlaenius) albissoni Reitter, 1908, Philorhizus crucifer ssp. crucifer (Lucas, 1846), and Demetrias monostigma Samouelle, 1819.